Pengenalan ZPT Alami Untuk Budidaya Melon di Dusun Ngadilegi Desa Plintahan Kec. Pandaan Kab. Pasuruan - Tri Susiyanti; Galuh Akmal Yudistira Wibowo; Fadila Suryandika (Jurnal Informasi Pengabdian Masyarakat, 2024)
This community service activity aims to utilize natural ingredients such as shallots, bamboo shoots, and coconut water as an alternative phytohormone in the growth of melon plants cultivated by partners. The target of the implementation of community service activities is the Madulegi Farmer Group in North Ngadilegi Hamlet. The method used in this activity is in the form of FGD (Focus Group Discussion) which is carried out directly or face-to-face and demonstrates the making of natural growth regulatory substances from shallots, bamboo shoots, and coconut water. The farmers' response was very enthusiastic about the introduction of this natural growth regulator for melon cultivation. Farmers in Ngadilegi Hamlet can understand well about the materials and equipment needed, as well as the process of making and utilizing these natural growth regulatory substances. Through this activity, it is hoped that it can provide an alternative for farmers to utilize natural ggrowth regulatory substances with materials that are easily obtained around and are relatively cheap and safe, so as to increase melon productivity